A new search for thermotolerant yeasts, its characterization and optimization using response surface methodology for ethanol production - Arora, Richa; Behera, Shuvashish; Sharma, Nilesh K.; Kumar, Sachin (Frontiers in Microbiology, 2015)
The progressive rise in energy crisis followed by green house gas (GHG) emissions is serving as the driving force for bioethanol production from renewable resources. Current bioethanol research focuses on lignocellulosic feedstocks as these are abundantly available, renewable, sustainable and exhibit no competition between the crops for food and fuel. However, the technologies in use have some drawbacks including incapability of pentose fermentation, reduced tolerance to products formed, costly processes, etc. Therefore, the present study was carried out with the objective of isolating hexose and pentose fermenting thermophilic/ thermotolerant ethanologens with acceptable product yield. Two thermotolerant isolates, NIRE-K1 and NIRE-K3 were screened for fermenting both glucose and xylose and identified as Kluyveromyces marxianus NIRE-K1 and K. marxianus NIRE-K3. After optimization using FCCD (Face-centered Central Composite Design), the growth parameters like temperature and pH were found to be 45.17 oC and 5.49, respectively for K. marxianus NIRE-K1 and 45.41 oC and 5.24, respectively for K. marxianus NIRE-K3. Further, batch fermentations were carried out under optimized conditions, where K. marxianus NIRE-K3 was found to be superior over K. marxianus NIRE-K1. Ethanol yield (Yx/s), sugar to ethanol conversion rate (%), microbial biomass concentration (X) and volumetric product productivity (Qp) obtained by K. marxianus NIRE-K3 were found to be 9.3%, 9.55%, 14.63% and 31.94% higher than that of K. marxianus NIRE-K1, respectively. This study revealed the promising potential of both the screened thermotolerant isolates for bioethanol production.